Proteomics Analysis Suggests Mitochondria Disorders and Cell Death Lead to Spaghetti Meat Myopathy - Brian Bowker; Byungwhi Kong; Hong Zhuang; Janghan Choi; Majid Shakeri (Meat and Muscle Biology)
Spaghetti meat (SM) is a myopathy that affects the structural integrity of pectoralis major muscles in broilers and accounts for decreased meat acceptability and significant economic losses for the industry. The causative mechanisms have not been as extensively investigated as other myopathies such as wooden breast. Proteomics analysis allows for the investigation alterations in muscle composition. The aim of this study was to investigate proteins related to mitochondria function in SM using proteomics analysis. Severe SM and normal pectoralis major were collected from a broiler processing plant. The analysis identified 1903 proteins. Results suggested that SM exhibited greater cellular stress and cell death as evidenced by increased N-myc downstream-regulated gene 1, plastin 3, ribosomal protein L10, and calnexin (FDR < 0.05 for all). Increased cell stress potentially impacted nonsense meditated decay pathway (eliminates mRNA containing premature translation termination codons). The SM myopathy downregulated several compounds related to mitochondria function and glucose metabolism pathways including basic leucine zipper and w2 domains 2, eukaryotic translation initiation factor 3 subunit B, pyruvate kinase L/R, thioredoxin-dependent peroxide reductase mitochondrial, enolase 3, creatine kinase mitochondrial 2, succinate-CoA ligase GDP/ADP-forming subunit alpha1, calcium voltage-gated channel auxiliary subunit alpha2delta 1, and complement 1q binding protein C (FDR < 0.05 for all), indicating a disruption in energy production and cell health. Current results suggested that SM impaired energy production and mitochondria function and elevated cell death. Although this study provides valuable information regarding possible mechanisms involved in the SM myopathy, further investigations are required to fully understand the mechanisms and their connections to other vital pathways.